2021
DOI: 10.30699/jergon.9.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Using the Job-Demands-Resources (JD-R) Model in Predicting the Resilience of the Melli Bank Branch Employees of Kerman, Iran

Abstract: model to investigate the individual resilience and the factors affecting it in Melli Bank branch employees of Kerman, Iran. Methods:In this self-reported cross-sectional survey, 358 Melli Bank Branch Employees of Kerman city participated from August to December 2019. According to the JD-R model, the constructs including resilience, emotional intelligence, social support, and job stress, were selected as outcome, personal resource, job resource, and Job demand respectively and participants participated in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Previous researchers have found that managing emotions play an essential role in improving employee resilience (Fisher et al., 2019; Mohseni Takalu et al., 2021; Richard, 2020). For example, Di Fabio and Kenny (2015) suggested that managing emotions significantly improves employee coping ability to manage continuous restructuring at jobs and organizations and high job demands.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Previous researchers have found that managing emotions play an essential role in improving employee resilience (Fisher et al., 2019; Mohseni Takalu et al., 2021; Richard, 2020). For example, Di Fabio and Kenny (2015) suggested that managing emotions significantly improves employee coping ability to manage continuous restructuring at jobs and organizations and high job demands.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%